Synergies of dibutyl phthalate on high-fat diet can aggravate cardiac fibrosis/dysfunction and the protective effects of vitamin E and salidroside: A molecular toxicological study in Sprague-Dawley rats - Xiao Liang; Yang Wu; Qing Feng; Deyu Zhu; Qi Huang; Zhuangzhuang Wei; Ping Ma; Xu Yang; Cuiyu Bao; Xinyu Bao (Ecotoxicology and Environmental Safety, 2025)
Background: Dibutyl phthalate (DBP) is a pollutant associated with plastic contamination and is commonly used as a plasticizer. It is linked to various adverse health effects, including cardiovascular disease (CVD). There is an association between DBP and high-fat diet (HFD), with HFD also contributing to the development of CVD, including cardiac fibrosis. Cardiac fibrosis is characterized by chronic inflammation of myocardial tissue and is a significant contributor to CVD pathogenesis. Recent research provides evidence suggesting a potential link between environmental exposure to DBP and cardiac damage. However, it remains unclear whether DBP has a synergistic effect on HFD and whether the interaction between the two exacerbates cardiac fibrosis and dysfunction. Objectives: The aim of this study was to investigate the synergistic effects of DBP on cardiac fibrosis induced by HFD. Specifically, we elucidated the mechanisms underlying the synergistic effect of DBP on HFD-induced cardiac fibrosis, with a focus on oxidative stress, pyroptosis, and the disruption of hepatic lipid metabolism. Furthermore, we explored the protective effects of two antioxidants, salidroside (Sal) and vitamin E (VitE), against the exacerbation of cardiac fibrosis caused by the synergistic action of DBP and HFD. Methods: Male Sprague-Dawley (SD) rats were divided into ten groups: a blank control group (Saline); separate groups exposed to low, medium, and high doses of DBP (DBP0.01, DBP1, DBP50 mg/kg/day); a high-fat diet group (HFD); a synergy group combining high concentrations of DBP and a high-fat diet (DBP50 +HFD); and treatment groups with Vitamin E and salidroside (DBP50 +VitE, DBP50 +Sal, DBP50 +HFD+VitE, DBP50 +HFD+Sal). The entire experimental period lasted for 12 weeks. We assessed the effects of DBP and HFD on cardiac function using echocardiography, as well as their impact on the development of cardiac fibrosis through histopathological analysis of the heart. Additionally, we examined the histopathology of liver tissue, lipid levels (Total cholesterol, Triglycerides, High-density lipoprotein, Low-density lipoprotein, Very low-density lipoprotein, Oxidized low-density lipoprotein), oxidative stress biomarkers (Reactive oxygen species, Malondialdehyde, Glutathione), pyroptosis-related proteins (NLRP3, Caspase-1, GSDMD, Interleukin-1β, Interleukin-18), and serum metabolomics (Data Credibility Analysis, Metabolite Differential Analysis, Metabolic Pathway Analysis and Metabolism-related analysis). Results: Our findings revealed that, compared to the saline group, both the high-dose DBP group and the HFD group exhibited significant cardiotoxic effects, inducing alterations in oxidative stress markers (ROS, MDA, and GSH) and levels of pyroptosis-related proteins (NLRP3, Caspase-1, and GSDMD) in myocardial tissue. Concurrently, the high-dose DBP and HFD groups demonstrated notable endocrine-disrupting effects, triggering hepatic steatosis (H&E and Oil Red O) and hyperlipidemia (TC, TG, HDL, LDL, VLDL, and ox-LDL). Ultimately, the combined action of DBP and HFD exacerbated the progression of cardiac fibrosis (H&E and Masson) and dysfunction (Echocardiography). Furthermore, metabolomics results suggest that the relevant pathways and metabolites involved in the citrate cycle (TCA cycle), arginine biosynthesis, tryptophan metabolism, and linoleic acid metabolism may also play significant roles. However, intervention with the inhibitors vitamin E and salidroside demonstrated protective effects against these adverse outcomes. Notably, salidroside exhibited superior efficacy compared to vitamin E in ameliorating lipid metabolism disorders, indicating its potential for preventing and treating cardiac fibrosis and dysfunction exacerbated by the synergistic effects of DBP and HFD. Conclusion: This study reveals, for the first time, the synergistic effect of DBP on HFD-induced cardiac fibrosis and dysfunction, suggesting that salidroside has a protective effect against cardiac fibrosis. These findings provide new insights into the multifaceted mechanisms involved in the pathology of cardiac fibrosis induced by DBP and HFD, and offer potential intervention targets for the prevention and treatment of cardiac fibrosis and dysfunction exacerbated by the synergistic effects of DBP and HFD.